Influence of feed refrigeration technology on the prevention of oxidative processes - Cavallucci, Clarita; Beghelli, Daniela; della Casa, Giacinto; Ficca, Roberto; Farioli, Tiziano; Giuliani, Angelo (Progress in Nutrition, 2014)
As a result of issues arising from overheating and deterioration of feed in the silos of farmers during the summer months, company Gima SpA has installed on Pelleting Technology, a pilot plant of refrigeration. The goal of this research was to evaluate the effects of the refrigeration system of grain storage technology applied to the pelleting of feed. Temperature and humidity were controlled both, environment and pellet. The test was performed on two presses (C: control no refrigeration, R: with refrigeration) in a number of 36 concentrated in the period from June to September 2010. Environmental and pellet temperature and humidity were monitored. The results show significant statistical variations and positively related to treatment (P